Bleaching systems in domestic laundry detergents: a review. Issue 80 (2nd September 2015) - Bianchetti, Giulia O.; Devlin, Carolyn L.; Seddon, Kenneth R.
<x xml:space="preserve">Abstract</x> This review summarises the development of oxygen-based bleaching systems in domestic laundry detergents and highlights the current research targets in this area.